THE INFLUENCE OF COMMITMENT, ORGANIZATIONAL TASKS, AND MOTIVATION ON TEACHER WORK ACHIEVEMENT AND QUALITY MANAGEMENT AT THE AL-HUDA TULUNGBALAK ISLAMIC BOARDING SCHOOL, BATANGHARI NUBAN DISTRICT, EAST LAMPUNG - Sutijah; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This study was purposed on determining the state of teachers’ quality manajement organization commitment and achievement motivation in pondok pesantren Al- Huda subdistrict Batanghari Nuban Lampung Timur as an endeavour to enhance teachers’ performances. This research is a case study by employing descriptive quantitative approach. The data source is primary and secondary data which obtained through interview, observation, field note, and documentation. The data analysis was conducted into three stages, namely data reduction, data display, and conclusion drawing. The conclusion of the research is teachers’ organization commitment is not fully affect to teachers performances. It is due to the higher teachers’ achievement motivation to create one of the school objectives, so it can be stated that teachers performances is Good.